Study of Patient Pain Management after Heart Surgery - Mohammadreza Sattari; Mohammad Ebrahim Baghdadchi; Marzieh Kheyri; Hassan Khakzadi; Simin Ozar Mashayekhi (Tabriz University of Medical Sciences, 2013)
Purpose: To investigate postoperative pain control and analgesic use after heart surgery. Methods: 120 patients undergone heart surgery, randomly entered the study. Each patient was asked to score his pain intensity on visual analog scale (VAS) at four different occasions. Results: 120 patients aged 59 year-old; including 81 male were enrolled in the study. 69.2% had coronary artery disease and 16.7% had heart-valve problem. Main types of surgeries were coronary artery bypass surgery (70.5%) and valve repairement (23%). Duration of ICU stay was 4.78±2.7 days and duration of intubations was 17.38 ± 36.46 hours. Pre-surgery pain relief was administrated to 42% of the subjects and morphine and promethazine was the main pre-surgery analgesia medication. Post surgery analgesic included morphine (injection), petidine (injection) and NSAIDS (oral or rectal). According to VAS, mean pain level, 1 and 4 hours after extubation, and before and one hour after transferring to wards was 5.05±2.5, 4.09±2.0, 3.52±1.8, 2.36±1.89, respectively. Although the level of pain reported was mostly moderate, 80% were reported satisfaction with their post-surgery pain management. Conclusion: A closer pain management control is needed for patients after heart surgery. Introduction of newer pain management techniques, medications and dosages could reduce the pain and suffering.